The gardens of Saba - Khan, Saniyasnain; Gurmeet (Goodword Books New Delhi)
"The Gardens of Saba" is a captivating tale inspired by the ancient Kingdom of Saba, known for its prosperity and lush landscapes. The story revolves around the mythical gardens that were said to be filled with exotic plants and vibrant flowers, symbolizing abundance and beauty. It explores themes of love, loss, and the connection between nature and human emotions. As the characters navigate challenges and relationships, they discover the deeper meanings of life, harmony, and the importance of preserving the beauty of their surroundings. This enchanting narrative invites readers to reflect on their relationship with nature and the timeless pursuit of happiness and fulfillment.